The Phenomena of Flood Caused by the Seawater Tidal and its Solution for the Rapid-growth City: A case study in Dumai City, Riau Province, Indonesia - Kausarian, Husnul; Batara, Batara; Putra, Dewandra Bagus Eka (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
A strategic city located on the northern coast of Sumatera Island known as Dumai City. This city is a growth and industrial city that always increase everyday economically. This city faces the flood problem that not only from the excess water from the rain, but also from the phenomena of seawater tidal. The tidal should not reach the mainland for the ideal situation, but the urbanization and development problem made it happen. Field observation and satellite data analysis shows the problem that happened in this city, also find out the solution how to make the seawater tidal will not being the flood when it occurs. The flood caused by the inadequate drainage condition is exacerbated by the low awareness of people who still do not maintain cleanliness, a lot of garbage that accumulates in the drainage causing the process of water flow to be inhibited. Geologically, the base rock of Dumai City consists of sand and peat which logically is a good system to absorb water because sand and peat are materials that have high porosity. Topographically, the city of Dumai is at an average height of three meters above sea level, so in fact, this city could be spared from the flood caused by the tide when it occurs. The solutions that can be proposed for this city are making the rivers being clean with normalization, well-designed drainage, Watergate and making an artificial lake for sinking the tidal seawater.